Cross-Actor Collaboration in Environmental Governance - Pamungkas, Aditya Surya (Adaptive Governance Research, 2026)
Purpose: This study aims to examine cross-actor collaboration in environmental governance and its role in strengthening coordination, enhancing community participation, improving policy implementation, and addressing institutional challenges at the local level. Subjects and Methods: This research employed a qualitative descriptive case study approach. Data were collected through semi-structured interviews, participant observation, and document analysis involving government officials, NGOs, academics, community leaders, environmental volunteers, and private sector actors. The data were analyzed using thematic analysis to identify recurring patterns and governance dynamics. Results: The findings indicate that collaborative environmental governance in Palu has improved stakeholder coordination and community participation through joint environmental programs and participatory initiatives. However, collaboration remains constrained by inconsistent communication, overlapping institutional authority, limited funding, and unequal organizational capacities. The study also found that trust-building and informal relationships among actors significantly strengthen collaborative practices and improve governance effectiveness. Conclusions: Effective environmental governance in Palu depends on sustainable institutional coordination, active community engagement, continuous communication, and long-term trust among stakeholders to support environmental sustainability and resilience.